Não neutralidade da ciência-tecnologia: problematizando silenciamentos em práticas educativas relacionadas à CTS - Rosa, Suiane Ewerling da (2014)
The STS movement has as a main objective the democratization of decision-making on social issues involving science-technology (ST). Also, this arises in contexts in which the supposed neutrality of ST began to be questioned. Neutrality understood as legitimizing technocratic decision models. In the educational field, I seek curriculum geared toward to the creation of a culture of participation, based on reference Freire-STS and LATSTS (Latin American Thought in Science Technology Society). As well, my research problem was: Historic Buildings, called myths, in other words, the supposed neutrality / superiority of technocratic decision model, the Salvationist perspective / redeeming attributed to ST and scientific-technological determinism, sustained and feeding back the supposed neutrality have been worked on educational practices related to the Science-Technology-Society? Which referrals have been given? The objectives that guided the research were: i) identify, in educational practices presented in the literature of the area, the approaches given to the three historic buildings; ii) analyze and deepen the featured aspects in regard to the three historic buildings, in a vision of non-neutrality of ST; and iii) signal parameters to Science Education in order to support proposals for educational practices. Methodologically, consisted of a qualitative research, bibliographic nature, being the corpus of analysis consisting of six articles published in journals in the field of Science Education. I used the Textual Discourse Analysis, which resulted in three categories of analysis: a) Silencing on the design of ST may be signaling an endorsement to a close understanding of the scientific-technological determinism; b) Silencing on dimensions other natures, beyond the scientific-technological in decision-making processes; and, c) Silencing about the values internalized in the scientific-technological product.